Students’ Perception of The Use of Duolinggo for Learning English - Daniswara, Lingga; Sahuddin, Sahuddin; Putera, Lalu Jaswadi; Saputra, Agus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study aims to determine the perception of students majoring in English towards the use of the Duolingo for learning English and to find out which aspects of language improve after using the Duolingo for learning English. The population were 10 English Education Department students who had used or were currently using Duolingo. This research used quantitative method. In collecting the data, this research used a questionnaire. The results of this research showed that most students liked and enjoyed using the Duolingo application for learning English. The students were asked questions regarding their perceptions of Duolingo, particularly about the elements of utility, content, context, control, and connectivity or mobility, and almost all agreed that they liked the Duolingo app because various aspects of it aligned with these five elements. Moreover, most students agreed that Duolingo helped them improve some aspects of their English skills, such as improving their pronunciation, writing, listening, speaking, and vocabulary. Based on the results, it can be concluded that the majority of students have a positive perception of using the Duolingo app for learning English.